2008
DOI: 10.1037/0090-5550.53.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the PHQ-9 screen for depression across time since injury among persons with spinal cord injury.

Abstract: The overlap of somatic-depressive symptoms and physical sequelae of spinal cord injury (SCI) has raised concerns regarding the validity of depression screens used within the SCI population. The Patient Health Questionnaire-9 (PHQ-9) measure parallels Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.; DSM-IV-TR; American Psychiatric Association, 2000) criteria of major depression. The authors investigated PHQ-9 factor structure among persons with SCI at various times postinjury. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 33 publications
(43 reference statements)
14
99
0
3
Order By: Relevance
“…71 A longitudinal study from the SCI Model Systems 59 revealed similar proportions of people with probable major depressive disorder at 1 year after injury (20.6%) and at 5 years after injury (18.1%), although there was considerable individual change in depression status over time. A cross-sectional SCI Model Systems study 57 reported similar percentages of 20.7 at 1 year and 17.6 at 5 years after injury, but lower percentages of 12.1 at 15 years and 12.3 at 25 years after injury, suggesting a decrease of depressive symptoms over many years.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…71 A longitudinal study from the SCI Model Systems 59 revealed similar proportions of people with probable major depressive disorder at 1 year after injury (20.6%) and at 5 years after injury (18.1%), although there was considerable individual change in depression status over time. A cross-sectional SCI Model Systems study 57 reported similar percentages of 20.7 at 1 year and 17.6 at 5 years after injury, but lower percentages of 12.1 at 15 years and 12.3 at 25 years after injury, suggesting a decrease of depressive symptoms over many years.…”
Section: Methodsmentioning
confidence: 91%
“…23,43,46,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] These estimates are affected by the type of instruments, choice of cutoff point (for example, possible, probable and major) and sample characteristics (gender, age and time after SCI). Craig (2009) 5 found five studies that applied a structured diagnostic interview during the rehabilitation or hospitalization phase, reporting 20-43% having minor or major depression disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Los análisis factoriales confirmatorios del PHQ-9 han registrado modelos con uno (28) y dos factores (32)(33)(34), sin que exista consenso con respecto a uno u otro. Sin embargo, en los trabajos de Elhai,et al (34), Krause,et al (33), y Richardson, et al (32), se evidenció que los modelos factoriales que consideraban el trastorno depresivo grave como un constructo conformado por dos factores (somático y no somático) presentaban un mayor ajuste estadístico que los de un solo factor.…”
Section: Dimensiónunclassified
“…Sin embargo, en los trabajos de Elhai,et al (34), Krause,et al (33), y Richardson, et al (32), se evidenció que los modelos factoriales que consideraban el trastorno depresivo grave como un constructo conformado por dos factores (somático y no somático) presentaban un mayor ajuste estadístico que los de un solo factor. Además, en estos estudios también se observó que los síntomas de trastorno depresivo grave detectados mediante el PHQ-9 se representaban mejor con un modelo que incluyera los factores somáticos y no somáticos que el simple modelo unidimensional.…”
Section: Dimensiónunclassified
“…4 Several studies have addressed the factor structure of depressive symptoms after SCI using the Patient Health Questionnaire-9 (PHQ-9), 7 a nine-item self-report measure intended to assist in identification of major depressive disorders (MDD). It has been used in a number of recent studies with SCI, [8][9][10] as well as with traumatic brain injury 11 and stroke. 12 Because the PHQ-9 items are based on the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) 13 criteria for major depression, assessing the factor structure has the potential to differentiate somatic items from non-somatic ones.…”
Section: Introductionmentioning
confidence: 99%